2016
DOI: 10.18632/oncotarget.10842
|View full text |Cite
|
Sign up to set email alerts
|

Metformin increases PDH and suppresses HIF-1α under hypoxic conditions and induces cell death in oral squamous cell carcinoma

Abstract: BackgroundMetformin is a biguanide, belonging to the oral hypoglycemic agents and is a widely used in the treatment of type 2 diabetes. Evidence indicate that Metformin inhibits cell proliferation in several human cancers and inhibits the Warburg phenomenon in tumor cells.ResultsLow PDH levels were observed in OSCC, and Metformin promotes an increase in PDH levels in hypoxic conditions. Metformin also reduced HIF-1α mRNA and protein levels. Metformin demonstrated antiproliferative effects, inhibited migration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 62 publications
3
66
1
Order By: Relevance
“…Metformin ameliorated high fat diet‐induced HIF‐1α expression in mice and reduced obesity‐associated fibrosis and inflammation in adipose tissue . Metformin reduced levels of HIF‐1α mRNA and protein in hepatocellular and squamous cancer cells . Metformin reduced HIF‐1α protein levels by suppressing mitochondrial respiration thereby reducing cellular hypoxia .…”
Section: Oral Hypoglycemic Agents As Potential Therapies For Hfpef Acmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin ameliorated high fat diet‐induced HIF‐1α expression in mice and reduced obesity‐associated fibrosis and inflammation in adipose tissue . Metformin reduced levels of HIF‐1α mRNA and protein in hepatocellular and squamous cancer cells . Metformin reduced HIF‐1α protein levels by suppressing mitochondrial respiration thereby reducing cellular hypoxia .…”
Section: Oral Hypoglycemic Agents As Potential Therapies For Hfpef Acmentioning
confidence: 99%
“…127 Metformin reduced levels of HIF-1α mRNA and protein in hepatocellular and squamous cancer cells. 128 Metformin reduced HIF-1α protein levels by suppressing mitochondrial respiration thereby reducing cellular hypoxia. 129 Metformin improved diastolic function in diabetic rats.…”
Section: Oral Hypoglycemic Agents As Potential Therapies For Hfpef mentioning
confidence: 99%
“…Metformin reduces production of ROS (reactive oxygen species), oxidative stress and DNA damage through the inhibition of mitochondrial complex I [2, 35,54].…”
Section: Metformin and Mtor Pathwaymentioning
confidence: 99%
“…Recent studies have showed that the anti-diabetic drug, Metformin, inhibited the cell proliferation and induced cell death in several human cancers such as prostate cancer, [10] breast cancer, [11] and OSCC. [12] Moreover, metformin has a synergistic antitumor effect when used in combination with other well-known chemotherapeutic agents such as cisplatin, 5-fluorourasil, and paclitaxel. [13][14][15] Dichloroacetate is widely used in the treatment of lactic acidosis, inhibits pyruvate dehydrogenase kinase (PDK) via phosphorylation of pyruvate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%